Consuming the tiger : anecdotes, anatomy and advertising in twentieth century Singapore - Teoh, Vincent Jin Keong (Nanyang Technological University, 2020)
Even though tigers were beginning to become extinct in Singapore by the turn of the twentieth century, the animal was still conspicuously utilised in advertisements and marketing materials by commercial companies to promote their products or services. This paper seeks to explore the use of tigers in marketing materials of three Singapore-based companies, namely the Raffles Hotel, Tiger Balm and Tiger Beer, as an entry into a broader analysis of their advertisements. The paper illustrates the multifaceted image of the tiger that was portrayed and consumed differently when appealing to Western and Asian audiences. The practice of market segmentation can further be observed as these companies personalised their marketing materials, beyond tiger portrayals, to enhance the appeal of their offerings to consumers of different groups.